Glycan signatures for the identification of cisplatin‐resistant testicular cancer cell lines: Specific glycoprofiling of human chorionic gonadotropin (hCG). (19th January 2022) - Hires, Michal; Jane, Eduard; Kalavska, Katarina; Chovanec, Michal; Mego, Michal; Kasak, Peter; Bertok, Tomas; Tkac, Jan
Abstract: Background: Testicular cancer (TC) is the most frequent type of cancer among young men aged between 15 and 34 years. TC is treated using cisplatin, but 3%–5% of TC patients fail to respond to cisplatin, with a very bad to fatal prognosis. Accordingly, it is most important to quickly and readily identify those TC patients who are resistant to cisplatin treatment. Methods: This study seeks to investigate changes in the glycosylation associated with cisplatin resistance to TC cell lines. Results: A specific glycoprofiling of human chorionic gonadotropin (hCG) was analysed in three TC cell lines and one cell line of female origin. A typical calibration curve for hCG glycoprofiling showed a dynamic range up to 50 ng/ml, with a limit of detection of 0.3 ng/ml and assay reproducibility represented by relative standard deviation of 3.0%. Changes in the glycan signatures on hCG were analysed in cisplatin‐sensitive cell lines and in their cisplatin‐resistant sub‐lines using an enzyme‐linked lectin assay (ELLA) protocol. An immobilised antibody was applied to a selective capture of hCG from a cytoplasmic fraction of cell lysates with final incubation using a lectin from a panel of 17 lectins. Conclusion: The results suggest that one particular lectin Dolichos biflorus agglutinin (DBA) can selectively discriminate sensitive TC cell lines from resistant TC cell lines. Moreover, there are additional lectins which can provide useful information about the strength of cisplatin resistance. Abstract : This is the first study focused on the use of a specific glycoprofiling of hCG using a panel of lectins for the investigation of glycosylation changes associated with TC or associated with cisplatin resistance. We identified DBA lectin as the most perspective one to evaluate resistivity of TC lines. Moreover, we found some lectins, which can be applied for positive correlation between lectin binding to hCG and cisplatin IC50 values for the sensitive cell lines and for the resistant cell lines.